2021
DOI: 10.1186/s42269-021-00506-0
|View full text |Cite
|
Sign up to set email alerts
|

Identity and prevalence of wheat damping-off fungal pathogens in different fields of Basrah and Maysan provinces

Abstract: Background Wheat is the most consumed cereal crops in the world infected by several pathogens and pests causing significant losses. The most threatening pathogens are fungi which cause serious diseases on roots, leaves and heads as one of the most threatening pathogens in specific wheat-growing countries. This study aimed to identify and evaluate the prevalence of damping-off fungal pathogens in different wheat fields at Basra and Maysan provinces. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The isolates of pathogenic fungi Rhizoctonia solani, Fusarium solani and Macrophomina phaseolina were isolated from the root and soil of wheat plant according to Abass et al (2021). In addition, the two fungi Trichoderma koningii and Chaetomium globosum were obtained from the Laboratories of the Prevention Department/College of Agriculture/University of Basrah.…”
Section: Sources Of Fungal Isolatesmentioning
confidence: 99%
“…The isolates of pathogenic fungi Rhizoctonia solani, Fusarium solani and Macrophomina phaseolina were isolated from the root and soil of wheat plant according to Abass et al (2021). In addition, the two fungi Trichoderma koningii and Chaetomium globosum were obtained from the Laboratories of the Prevention Department/College of Agriculture/University of Basrah.…”
Section: Sources Of Fungal Isolatesmentioning
confidence: 99%
“…Moreover, downstream processing of the secretome requires less purification steps. It has also been reported that M. phaseolina also infects wheat seeds ( Abass et al, 2021 ). Thus, the putative virulence factors that were identified in the present study may help to deduce the infection mechanisms involved in other susceptible host plants.…”
Section: Discussionmentioning
confidence: 85%
“…Plant pathogenic fungi have the largest proportion of secreted proteins. M. phaseolina also infects wheat seeds ( Abass et al, 2021 ). In order to isolate the secretome of M. phaseolina , the fungal spore suspension was inoculated in a wheat bran matrix maintaining optimum temperature and relative humidity.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the longevity of M. phaseolina sclerotia and an almost 60-year-long four-crop (sugar beet, sunflower, corn, and wheat) agricultural system in Rimski Šančevi, with all listed crops having been reported as hosts of this pathogen, it is likely that the experimental field is highly contaminated with the sclerotia of M. phaseolina (Jacobsen, 2006;Babu et al, 2007;Abass et al, 2021;Marquez et al, 2021). The crop rotation practice applied in the experimental field is similarly applied in the wider area of Serbia, producing an environment that contributes to the problem.…”
Section: Discussionmentioning
confidence: 99%